Judging and politics - Mhlaba, Mabalana Wilson (University of Limpopo, 2007)
Refer to the document
Thesis (Ph. D. (Law)) -- University of Limpopo, 2007
Keywords: Judging; Politics; Justice, Administration of-Political aspects -- South Africa.; Justice and politics -- South Africa